2018
DOI: 10.1371/journal.pone.0192252
|View full text |Cite
|
Sign up to set email alerts
|

Administration of L-arginine plus L-citrulline or L-citrulline alone successfully retarded endothelial senescence

Abstract: L-citrulline and L-arginine supplementation has been shown to have several beneficial effects on the cardiovascular system. Nitric oxide (NO) protects against the progression of atherosclerosis and is synthesized by nitric oxide synthase (NOS), which converts L-arginine (L-Arg) into L-citrulline (L-Cit). Our previous study revealed that chronic administration of a combination of L-Cit and L- Arg has a better therapeutic effect on high cholesterol-induced atherosclerosis in rabbits. We investigated how L-Arg an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…32) L-Citrulline has been reported to retard high glucose-induced endothelial senescence in combination with arginine. 33) Arginine is considered as a potential source of energy in ADI pathway by bacteria, because it forms one molecule of ATP from per mole arginine consumed during the production of ornithine and ammonia. 34) A research group has reported that a function of the ADI pathway is acid-based physiology within the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32) L-Citrulline has been reported to retard high glucose-induced endothelial senescence in combination with arginine. 33) Arginine is considered as a potential source of energy in ADI pathway by bacteria, because it forms one molecule of ATP from per mole arginine consumed during the production of ornithine and ammonia. 34) A research group has reported that a function of the ADI pathway is acid-based physiology within the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the intake of citrulline may contribute to the increase of arginine oral bioavailability. 32) Additionally, when arginine is orally administrated in combination with citrulline, the arginine can also pass through the GIT and hepatic tissue without undesirable metabolization by those organisms. 32) This is because L-citrulline inhibits the arginase activity by acting as an allosteric inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have also linked L-Cit induction of NO production alongside with its anti-oxidant ability. L-Cit directly attenuated ROS production by downregulating the protein expression levels of p67 phox , a critical component for NADH/NADPH superoxide generation [77]. In vitro studies using asymmetric dimethylarginine (ADMA), a non-selective NOS inhibitor, demonstrated L-Cit effectiveness to restore NO production and attenuate nitrosative stress [78].…”
Section: Anti-oxidant Statusmentioning
confidence: 99%
“…Researches have also linked L-Cit induction of Nitric oxide production alongside with its anti-oxidant ability. L-Cit directly attenuated ROS production by downregulating the protein expression levels of p67 phox , a critical component for NADH/NADPH superoxide generation (90). In vitro studies using asymmetric dimethylarginine (ADMA), a non-selective NOS inhibitor, demonstrated L-Cit effectiveness to restore NO production and attenuate nitrosative stress (91).…”
Section: Anti-oxidant Statusmentioning
confidence: 99%